2009
DOI: 10.3109/00016480802660510
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological analysis of malignant carotid body tumour: a report of nine cases

Abstract: The carotid artery was blocked in three patients. In one of these the artery was reconstructed with a vascular prosthesis, while two underwent carotid ligation. Eight patients suffered from a cranial nerve dysfunction (defect) and two suffered postoperatively from a hoarse voice, four had a glossal deviation, five had Horner's syndrome and one had a deviation of the lip angle. One patient had a congestive cough. The histopathological diagnosis in all nine cases was MCBT. One patient had metastases to a cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
1
18
1
5
Order By: Relevance
“…This frequency was compatible with previous reports (4)(5)(6)(7)21). It is well known that, as histopathological examination cannot distinguish a malignant tumor by morphological features in microscopic findings, malignancy or not is diagnosed by metastatic activity, namely clinical findings.…”
Section: Shamblin Classification ------------------------------------supporting
confidence: 80%
“…This frequency was compatible with previous reports (4)(5)(6)(7)21). It is well known that, as histopathological examination cannot distinguish a malignant tumor by morphological features in microscopic findings, malignancy or not is diagnosed by metastatic activity, namely clinical findings.…”
Section: Shamblin Classification ------------------------------------supporting
confidence: 80%
“…4 In 6% to 12.5% of cases, CBTs have malignant potential and tend to grow and invade locally, causing symptoms. 5 We have reported our use of the retrocarotid dissection technique in the surgical treatment of benign CBTs, and the substantially shorter procedural times and hospital stays in comparison with using the standard caudocranial technique. 6 Here, we describe our first 2 cases of malignant Shamblin III CBTs resected by means of retrocarotid dissection.…”
mentioning
confidence: 99%
“…Intraoperatively, it is possible to see local metastasis to the lymph nodes in the neck. Zhang and colleagues, 5 who evaluated clinical and pathologic features in 9 cases of malignant CBT, found that these tumors were firm and larger than benign tumors; furthermore, the carotid artery generally could not be palpated because of tumor encasement (8 of the neoplasms were Shamblin III). 5 Malignant CBTs metastasize mainly to regional lymph nodes, and also to the lungs, bones, liver, breasts, pancreas, kidneys, and brain.…”
mentioning
confidence: 99%
See 2 more Smart Citations